The impact of food safety regulatory information intervention on enterprises’ production violations in China: a randomized intervention experiment - Zhao, Tong; Li, Taiping; Liu, Dan; Luo, Yun (Frontiers in Sustainable Food Systems, 2024)
The prevalence of unsafe food poses a widespread challenge across numerous nations. Despite the continuous investments by the Chinese government in food safety regulation, the condition of food safety in China is still not ideal and requires substantial enhancements. Cost-effective, informationbased strategies are essential for the effective management of food safety hazards. In this research, we established an extensive database of food enterprises with documented violations and carried out a randomized intervention trial to assess the effects of regulatory information interventions on the decrease of production violations in these enterprises. The findings reveal that interventions based on food safety regulatory information were instrumental in diminishing production violations among food enterprises and had spillover effects within a given geographic area. It is important to note that the impact of the intervention was delayed, with noticeable results on production violations becoming apparent six months post-intervention. Additionally, the degree of information communication and the degree of information concern can positively moderate the reduction of food enterprises' production violation behavior by food safety regulatory information intervention.